Neonatal Encephalopathy Is Associated With Altered IL-8 and GM-CSF Which Correlates With Outcomes - Deirdre U. Sweetman; Deirdre U. Sweetman; Deirdre U. Sweetman; Tammy Strickland; Tammy Strickland; Ashanty M. Melo; Ashanty M. Melo; Lynne A. Kelly; Lynne A. Kelly; Lynne A. Kelly; Chike Onwuneme; Chike Onwuneme; et al. (Frontiers Media S.A., 2021)
Aim: To investigate the relationship between cytokines associated with innate immune cell activation and brain injury and outcome in infants with NE compared to neonatal controls.Methods: Serum and CSF biomarkers associated with activated neutrophils and monocytes [Interleukin-8 (IL-8) and Granulocyte-Macrophage-Colony-Stimulating-Factor (GM-CSF)] were serially measured using duplex immunoassays on days 1, 3 and 7 in term newborns with NE and controls. Results were compared to grade of encephalopathy, seizures, MRI brain imaging, mortality and Bayley Score of Infant and Toddler Development (Bayley-III) at 2 years of age.Results: Ninety-four infants had serum samples collected with 34 CSF samples. NE Grade II/III was significantly associated with elevated on day 2 serum IL-8. Mortality was best predicted by elevated day 1 IL-8. GM-CSF was initially elevated on day 1 and abnormal MRI imaging was associated with decreased day 2 GM-CSF. Elevated GM-CSF at day of life 6-7 correlated negatively with composite cognitive, language and motor Bayley-III scores at 2 years.Conclusion: Moderate or severe NE and mortality was associated with elevated IL-8. Day 2 GM-CSF could predict abnormal MRI results in NE and Bayley-III. Therefore, these cytokines are altered in NE and may predict early outcomes and further implicate inflammatory processes in NE.